Effects of short-term moderate hypoxic exposure during sleep on maximal aerobic capacity at high altitude - Maekawa, T.; Yamamoto, M. (13. International Hypoxia-Symposium, February, 19-22, 2003, Banff, Alberta (Kanada), 2003)
Seven male college students were subjected to shortterm, intermittent (only during sleep) hypoxic exposure (IHE) in a normobaric hypoxic room set at a moderate altitude (equivalent to an altitude of 2,000 m; O2 5 16.4%), and the effects of the IHE on maximal aerobic capacity at high altitude (equivalent to an altitude of 4,000 m; O2 5 12.7%) were examined. Hypoxic exposure was for 4 days. Each day the subjects slept for 7 hours in the hypoxic room, and the rest of the time they spent at sea level. No exercise at all was performed in the hypoxic environment. Before and after the IHE, the subjects performed a multigraded exercise tolerance test by pedaling at the simulated 4,000 m altitude. Results showed that after this IHE, maximal oxygen uptake (VO2max) and maximal workload at an altitude of 4,000 m significantly increased. Expired volume per minute at the point of VO2max significantly increased after the IHE. However, the red blood cell count and hematocrit level significantly decreased after the IHE, and it was surmised that temporary hemodilution had occurred. It can be said from these results that maximal aerobic capacity at high altitude improves even with short-term hypoxic exposure during sleep at a moderate altitude. It is important that hypoxic exposure to moderate (physiologically safe) altitude can improve work capacity at much higher (risky) altitude. Ad also, it is thought that this improvement was affected by ventilatory adaptation, and that the effects of negative changes in blood properties were small.